Pleiotropic effects of MORC2 derive from its epigenetic signature - Peymani, Fatemeh; Ebihara, Tomohiro; Smirnov, Dmitrii; Kopajtich, Robert; Ando, Masahiro; Bertini, Enrico; Carrozzo, Rosalba; Diodato, Daria; Distelmaier, Felix; Fang, Fang; Ghezzi, Daniele; Hempel, Maja; et al. (Brain, 2026)
Heterozygous missense mutations in MORC2 have been implicated in various clinical entities, ranging from early-onset neurodevelopmental disorders to late-onset neuropathies. The mechanism underlying the phenotypic heterogeneity and pleiotropic effects of MORC2 has remained elusive.Here, we analysed blood and fibroblast DNA methylation, transcriptomes, proteomes and phenotypes of 53 MORC2 patients.We identified a MORC2-specific DNA methylation episignature that is universal across all MORC2-associated phenotypes and conserved across different tissues. The MORC2 episignature consists mainly of DNA hypermethylation in promoter regions, leading to transcriptional repression of target genes resulting in a MORC2-specific RNA signature. Concomitant downregulation of three disease-associated genes—ERCC8, NDUFAF2 and FKTN—at different levels mirrors the variable biochemical defects and clinical manifestations observed in MORC2 patients. Silencing of NDUFAF2 accounts for the Leigh syndrome manifestation, whereas dysmorphic features are due to the repression of ERCC8.Overall, we showed that pathogenic MORC2 variants cause specific episignature, whereby methylation level variability and its repression impact on target genes explains the pleiotropy and predicts phenotypic heterogeneity in MORC2-related disorders. We predict that epigenetic variation may underlie pleiotropy in other Mendelian disorders.
Vorab veröffentlicht: 30. April 2025
Gesehen am 20.02.2026